1974
DOI: 10.1144/gsl.qjeg.1974.007.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Fissure patterns and slope failures in till at Hurlford, Ayrshire

Abstract: Summary The present investigations have shown that the till at Hurlford, Ayrshire, is fissured and that a very definite fissure pattern exists. The nature of the fissures and influence of weathering, overburden pressures and stress release have been established and new scalar property classification especially designed for tills have been successfully employed. A close relationship between fissure fabric, slope stability and directional shear strength characteristics has been found and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Scotland and the Midland Valley, translational slides are widespread in glacial drift on steep hillslopes, on the flanks of incised river valleys and in man-made cuttings (for example, those bordering the M90 c. 1 km north of the Forth Bridge), but aside from the appearance of occasional 'undifferentiated' landslides in drift on Geological Survey maps in which debris flow activity is known to have occurred and discussion of isolated examples induced by excavation (McGown et al, 1974;Clark et al, 1979), such failures have largely gone unrecorded. The same is true of the many small translational slides that occur on steep hillslopes and river valleys in the Southern Uplands.…”
Section: Category 4: Shallow Translational Slides In Drift or Regolithmentioning
confidence: 99%
See 1 more Smart Citation
“…Scotland and the Midland Valley, translational slides are widespread in glacial drift on steep hillslopes, on the flanks of incised river valleys and in man-made cuttings (for example, those bordering the M90 c. 1 km north of the Forth Bridge), but aside from the appearance of occasional 'undifferentiated' landslides in drift on Geological Survey maps in which debris flow activity is known to have occurred and discussion of isolated examples induced by excavation (McGown et al, 1974;Clark et al, 1979), such failures have largely gone unrecorded. The same is true of the many small translational slides that occur on steep hillslopes and river valleys in the Southern Uplands.…”
Section: Category 4: Shallow Translational Slides In Drift or Regolithmentioning
confidence: 99%
“…Insufficient data therefore exist on the distribution of category 4 landslides to allow them to be associated with particular lithologies, drift deposits or topographic circumstances on a regional scale, though the comments made above regarding the distribution of debris flow activity in the Highlands may Downloaded by [Queen Mary, University of London] at 00:14 11 October 2014 be pertinent. Recorded instances of translational failure in unconsolidated sediments tend to be associated with intensive rainstorms following prolonged periods of wet weather, which suggests that antecedent moisture conditions are critical (Common, 1954), or with excavation (McGown et al, 1974;Clark etai, 1979).…”
Section: Category 4: Shallow Translational Slides In Drift or Regolithmentioning
confidence: 99%
“…(10) and GA, the parameters of the models are obtained: n=3; {k 1 , k 2 , k 3 }={1.800, 2.989, 7.000}; {N 1 , N 2 , N 3 }={4, 8, 5};{b 1 , b 2 , b 3 }={2, 50, −0.06}. Using these parameters, mathematic simulation was conducted.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…MCGOWN et al [10] conducted a great deal of shear tests on soil samples with different sizes, and used several kinds of regression curves to fit the relationship between shear strength and size of sample, the following equation is the most satisfying one: 1 2 3 exp( ) f a a a r = +…”
Section: Relationship Between Needed Time For Slacking and Grain Sizementioning
confidence: 99%
“…These fractures suggest that the maximum stress did not act parallel to the ground surface but acted along a direction with a certain dipping angle from to the ground surface. McGown et al, (1974) also reported that the pattemed vertical fractures in a till were caused by directional lateral stress of which the principal stress in the tills of Hurlford, Ayrshire coincided roughly with drumlin orientation. Although soil lateral stresses have been considered isotropic for many soils, the previously stated case in glacial tills shows that the lateral stress may be anisotropic.…”
Section: Fracture Formation Case Studiesmentioning
confidence: 95%